Clinical implementation of long-acting antiretroviral treatment in high-income countries: challenges and advantages. Issue 3 (18th May 2022) - Waters, Laura; Sparrowhawk, Alex
Abstract : Purpose of review: Long-acting antiretroviral therapy (LA-ART) brings a paradigm shift to HIV care with injectable cabotegravir/rilpivirine (IM-CAB/RPV) in current or imminent use in several countries. This brings the usual opportunities and challenges of a new therapy, plus requirements to adapt services to reliably deliver injections and ensure patients understand advantages and limitations. We summarise key considerations for implementation in high-income countries. Recent findings: Monthly IM-CAB/RPV is noninferior to oral ART and monthly IM-CAB/RPV to 1-monthly in carefully selected virally suppressed people. The numerically higher virological failure rate on two-monthly IM-CAB/RPV warrants close attention and careful monitoring. Implementation projects report positive experiences for patients and staff, but also barriers. Data is needed in younger people, pregnancy/breastfeeding, and in those with detectable viraemia secondary to suboptimal adherence. Summary: We highlight a paucity of real-world data and key unanswered questions. Existing data on injection techniques may have implications for training; monitoring of outcomes is crucial to ensure clinical trial results are replicated in real-life. Better understanding of treatment failure, and individualised therapy, is crucial, and it is important to repeat patient preference surveys as new data emerges to ensure decisions are based on the most recent evidence of benefit vs risk.